(untitled) (Hematology Meeting Reports, 2009)
4-Phenylamino-3-quinolinecarbonitriles have been extensively studied by Wyeth as inhibitors of diverse kinases including EGFR, HER-2, and MEK.1,2 Screening of a library of 4-phenylamino-3-quinolinecarbonitriles with various substituents on the 4-phenylamino group identified 1 as an inhibitor of Src kinase3 (Scheme 1). Optimization of this screening lead led to SKI-606, currently in clinical trials for the treatment of solid tumors.4 Subsequent to the discovery that SKI-606 was a potent Src inhibitor, it was determined that this compound was also a potent inhibitor of Abl kinase.5